Outcome of antithrombotic therapy in cancer patients with catheter-related thrombosis: a systematic review - Yin, Qinan; Zheng, Xingyue; Han, Lizhu; Huang, Xuefei; Wang, Yueyuan; Song, Yujie; Zhang, Yuan; Bian, Yuan (Frontiers in Cardiovascular Medicine, 2023)
The guidelines' recommendations for anticoagulation in cancer patients with catheter-related thrombosis are unclear. The aim of this systematic review was to assess anticoagulation management in cancer patients with catheter-related thrombosis (CRT) based on previously published studies. As of June 10, 2023, we searched databases including PubMed, Embase, and Cochrane and included 11 observational studies that met the criteria. We evaluated 770 adults with active cancer and objectively confirmed patients with CRT who were using drugs including warfarin, LMWH, and new oral anticoagulants as antithrombotic therapy. We extracted outcome data, including thrombosis recurrence, catheter dysfunction, major bleeding, and death, and performed a meta-analysis. In this study we found that the risk of VTE recurrence was higher with rivaroxaban, the risk of bleeding and death appeared to be greater with warfarin, and although the risk of catheter dysfunction due to